Ultrastructure features of the midgut of the female adult Amblyomma cajennense ticks Fabricius, 1787 (Acari: Ixodidae) in several feeding stages and subjected to three infestations - Caperucci, Debora [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
The digestive tract of Amblyomma cajennense, as well as other species of ticks, is divided into the anterior, medium and posterior intestines and is the organ responsible for digestion of blood ingested during the meal on the host. The anterior and posterior regions are derived from the ectoderm and the medium one from the endoderm. In the present ultrastructural study, we analyzed the midgut of females in a semi- and fully engorged stages, on the rabbit host, which was subjected to three infestations, where were analyzed the changes that the epithelial cells went through. The results showed that during the feeding period the outermost layer the intestine is composed of muscle fibres, as observed in those semi-engorged and engorged ones in the 1st infestation and semi-engorged in the 2nd infestation. The cytoplasm of digestive cells of feeding females, and those of the semi-engorged and fully engorged in the 1st, 2nd and 3rd infestations showed some intact regions (preserved organelles) with others were disorganized. Large lipid droplets and protein granules were observed in the cytoplasm of the cells of the intestine in all phases of feeding process. Cytoplasmic spherocrystals were only observed in the semi-engorged and engorged females in the 1st and 2nd infestations. Intense vacuolation was observed in the digestive cells of the midgut of semi-engorged and engorged A. cajennense females in the 2nd infestation and those engorged in the 3rd infestation. The data showed that the gut of the females of the A. cajennense tick is actually going through big changes during the feeding period, which become more pronounced when reinfesting. These changes are probably due to the host immune response that returns antibodies to the ectoparasite and thus acquires resistance to their secreted products. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Amblyomma cajennense; Ticks; Midgut; TEM; Reinfestation; Resistance; Feeding process